Selection signature analysis using whole genome resequencing data reveals candidate genes for white plumage color in Korean native ducks - Jaewon Kim; Jaegwon Kim; Eunjin Cho; Sunghyun Cho; Minjun Kim; Won-Hyung Chung; Jung-Woo Choi; Hyo Jun Choo; Jun Heon Lee (Animal Bioscience, 2025)
Objective Domestication alters the phenotypes of wild animals to meet human demands and leaves characteristic patterns in their genomes. Various selection signature analysis methods have been developed to identify these characteristic patterns left in the genome. The Korean native duck (KND) is one of the domesticated species in Korea. KND is categorized into two populations based on plumage color; colored KND (KNDC) and white KND (KNDW). To enhance the competitiveness of native ducks, it is necessary to establish a KNDW line. In this study, we conducted selection signature analysis to identify candidate genes associated with white plumage color in KNDs. Methods We generated whole genome resequencing data from 22 KNDCs, 22KNDWs, and 10 Pekin ducks (PKDs). To detect distinct genomic regions between KND populations with different plumage colors, we analyzed three types of selection signature analysis: the fixation index (Fst), nucleotide diversity(π), and cross-population extended haplotype heterozygosity (XP-EHH). Results Population structure analysis showed that although KNDC and KNDW are distinct from PKD, they form a single group sharing a common ancestor. The results of Fst and π analyses revealed that compared to KNDC, there were strong selection signals in the MITF gene in KNDW, with a 6,641 bp insertion in the intron 2 region. This variant is a transposable element insertion that causes white plumage in PKD. In addition, XP-EHH analysis identified DCT, KIT, TYR, and ADCY9 as major candidate genes associated with pigmentation in the KND population. Conclusion White plumage in KNDW is caused by a transposable element insertion in the MITF gene. This finding improves our understanding of plumage color in KND and supports the establishment of KNDW breeding programs.